Hazarat Zakariyah (AS) - Karam ,Ambia (Lahore , Karachi children's publication)
In the Quran. According to the Quran, Zakariya was said to be a priest and prophet of God whose office was in the Second Temple in Jerusalem. He would frequently be in charge of managing the services of the temple and he would always remain steadfast in prayer to God .